PEMASARAN POLITIK GERAKAN PEMILIHAN PRESIDEN SATU PUTARAN DAN IMPLIKASINYA - Nurhayani Saragih (Indonesian Journal of Dialectics, 2012)
The research aims are to identify and to analyze the activity of political consultant. Unit analysis of this research is the medianews concerning the activities of Lingkaran Survey Indonesia (LSI) political consultant during presidential election campaign on the first round on 2009. The research shows: LSI published 3 researches. LSI target are: 1) demography are grassroots. 2)geography are located in DKI Jakarta, Jawa Barat, Banten, Jawa Tengah, Jawa Timur, Sumatera Utara, Sulawesi Selatan. 3) thepsychographys are: silent majority and swing voter (they did not know who will be elected as president yet). Marketing mix: 1) pull marketing strategy through Perhimpunan Peduli Indonesia (PPI) with 2.800 volunteer. 2) push marketing strategy by advertising and press conference. Conclusion: 1) Campaign the political processes ethically are not allowed. 2) LSI not informed from the beginning that they were SBY-Boediono political consultant. 3) Presidential election campaign on the first round are the consultant strategy to win their client on campaign. Not civil society movement, as they campaigned.